2020
DOI: 10.1111/adj.12759
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Adult Oral Health 2017–18: participation and representativeness

Abstract: The National Study of Adult Oral Health (NSAOH) 2017–18 collected information from a sample of the Australian population aged 15 years and over. The Study comprised an interview questionnaire, completed by telephone or online, and an oral epidemiological examination among dentate participants. Participation in the Study was voluntary and therefore relied on the goodwill of selected participants. This paper provides a summary of participation rates for the Interview and Examination phases of the study. The pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Descriptive statistics were performed on STATA/SE 17.0. To make population-level inferences, all the estimates were weighted to the Australian population [for further details on survey weighting procedures see Ellershaw et al (2020) ]. The proportion and 95% confidence intervals for each policy response were estimated by socio-demographic group.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were performed on STATA/SE 17.0. To make population-level inferences, all the estimates were weighted to the Australian population [for further details on survey weighting procedures see Ellershaw et al (2020) ]. The proportion and 95% confidence intervals for each policy response were estimated by socio-demographic group.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were carried out on the 5,022 adults who were examined. Information on the NSAOH 2017‐18 study aims and methods 7 and study participation and weighting 9 can be found elsewhere. This study followed the STROBE Statement for reporting cross‐sectional studies.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed information on the sample design, study participation, reliability, sampling variability and development of population weights is reported elsewhere. 23,24 The project was reviewed and approved by The University of Adelaide's Human Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Persons selected were invited to respond to a questionnaire either online or through a computer‐assisted telephone interview. Detailed information on the sample design, study participation, reliability, sampling variability and development of population weights is reported elsewhere 23,24 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation